Gender differences in bifurcation percutaneous coronary interventions: Update from the Prospective Global Registry for the Study of Bifurcation Lesion Interventions (PROGRESS-BIFURCATION) - Uluganyan M. (My University, 2024)
Background:Gender differences on short and long-term outcomes following bifurcation percutaneous coronary intervention (PCI) have received limited study.Research Questions:To examine gender differences in outcomes of bifurcation PCI.Methods:We examined the angiographic, procedural characteristics, and outcomes of 1084 bifurcation PCIs (1076 patients) performed at five centers between 2013-2024 from the Prospective Global Registry for the Study of Bifurcation Lesion Interventions (PROGRESS-BIFURCATION).Results:Women represented 25.19% of the entire study population. They were older (68.37±12.34 vs 66.09±11.54; p=0.001), less likely to be currently smokers (13.7% vs 20.4%; p=0.014), with higher left ventricular ejection fraction (%) (55.46±13.27 vs 53.16±12.55; p<0.001) and lower baseline creatinine (0.85 vs 1.00; p<0.001). Lesion characteristics were mostly similar, with slightly lower proximal and distal main vessel diameter in women. Their proximal main vessel was more likely to be left anterior descending artery (46.5% vs 39.4%; p=0.030) and less likely to be right coronary artery (10.3% vs 16.1%; p=0.030), compared to men. Technical success was similar (94.5% vs 94.6%; p=0.952), while procedural success was lower (89.6% vs 94.1%; p=0.011). In-hospital major adverse cardiac events (MACE) were more common in women (8.5% vs 4.2%; p=0.007), which presented with increased in-hospital mortality (4.1% vs 0.6%; p<0.001), stroke (1.8% vs 0.1%; p=0.005) and bleeding (1.8% vs 0.2%; p=0.013). Their PCIs required equal procedure time, but lower fluoroscopy time, contrast volume and air kerma radiation dose. Female gender was independently associated with higher in-hospital major adverse cardiac events (MACE) (odds ratio (OR) 2.21; 95%CI 1.23-3.95; p=0.008) and lower procedural success (OR 0.56; 95%CI 0.32-1.00; p=0.044). Follow-up data were available for 733 patients (68.12%). The incidence of follow-up MACE was significantly higher in women (hazard ratio (HR) 1.36; 95%CI 1.02-1.81; p=0.038), while on adjusted mixed Cox proportional hazards analysis female gender was associated with higher follow-up MACE (HR 1.58; 95%CI 1.08-2.30; p=0.018). The incidence of follow-up mortality was similar between genders (HR 1.17; 95%CI 0.78-1.77; p=0.45).Conclusions:Bifurcation PCI can be accomplished with high technical success in women, but higher in-hospital and follow-up MACE, compared to men.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (Med); Clinical Medicine (Med)